Paradoxical activation of chronic lymphocytic leukemia cells by ruxolitinib in vitro and in vivo - Spaner, David E.; Luo, Tina YuXuan; Wang, Guizhi; Schreiber, Gideon; Harari, Daniel; Shi, Yonghong (Frontiers in Oncology, 2023)
Chronic lymphocytic leukemia (CLL) is characterized by an aberrant network of cytokines that can support the growth of leukemia cells by triggering janus kinase (JAK)/STAT pathways. Targeting cytokine-signaling would seem to be a rational therapeutic strategy but the JAK inhibitor ruxolitinib failed to control and seemingly accelerated the disease in clinical trials. Ruxolitinib increased phosphorylation of IRAK4, an important toll-like receptor (TLR)-signaling intermediate, in circulating CLL cells in vitro and also increased p38 and NFKB1 phosphorylation while decreasing STAT3 phosphorylation in CLL cells activated with TLR-7/8 agonists and IL-2. Among the cytokines produced by activated CLL cells, high levels of IL-10 contributed strongly to STAT3 phosphorylation and inhibited TLR7 activity. Ruxolitinib limited TLR-mediated IL10 transcription and markedly reduced IL-10 production in vitro. It also decreased blood levels of IL-10 while increasing TNFα along with phospho-p38 expression and gene sets associated with TLR-activation in CLL cells in vivo. The bruton’s tyrosine kinase inhibitor ibrutinib deactivates CLL cells in vivo and also decreased IL-10 production in vitro but blocked initial IL10 transcription induced by TLR-signaling and decreased TNFα production. These findings suggest that possible benefits of inhibiting growth factors with JAK inhibitors in CLL are outweighed by negative effects on potential tumor suppressors such as IL-10 that allow unrestrained activation of NFkappaB by drivers such as TLRs. Specific inhibition of growth-promoting cytokines with blocking antibodies or infusing suppressive cytokines like IL-10 might be better strategies to manipulate cytokines in CLL.